Strategi Supervisi Pendidikan pada Era Digitalisasi - Rahmania Sadek; Djulaiha Abubakar (CV. Global Cendekia Inti, 2025)
Effective educational supervision strategies are key to improving the quality of education and facilitating the professional development of teachers in this ever-changing modern era. This study aims to analyze how educational supervision strategies can be optimized through the use of technology in the digital era. The research method used in this study is a literature review, which aims to analyze and review literature related to educational supervision strategies in the digital era. The results of this study indicate that educational supervision strategies play a crucial role in facing the dynamic changes in the digital era. The use of information technology in the learning process and the implementation of data-based assessment systems are essential elements that must be implemented. Thus, educational supervision strategies function as drivers of innovation that can create a more interactive and effective learning environment. Furthermore, the implementation of a sound change strategy approach is key to managing the educational transformation process. This involves collaboration between teachers, principals, and other stakeholders to create a shared vision regarding the desired direction of education. Therefore, educational supervision strategies need to continuously innovate and adapt to meet the demands and challenges of education in the digital era and make a significant contribution to educational quality.